THE EFFECT OF PERCEIVED JUSTICE TOWARD RECOVERY SATISFACTION AND TRUST: A STUDY ON HARRIS HOTEL & CONVENTIONS MALANG - Claudia Khoirunnissa Armiladiba (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
This research aims to determine the effect of Perceived Justice toward Recovery Satisfaction and Trust on study of Harris Hotel & Conventions Malang in simultaneously and via mediation. The research is explanatory research which explains the causal relation between the variables through hypothesis testing. The data collection technique of this study uses questionnaires and literature study.This study used 150 samples of Harris Hotel’s consumers in Malang. Those samples were taken using a purposive sampling technique. Test instrument that are used for testing the research instrument are validity test, reliability test, and classical assumption test. The analytical methods that were used are path model analysis and hypothesis testing are conducted with t test using SPSS 21.The result of this study shows with using testing t is concluded that each of Perceived Justice has significant and direct effect toward Recovery Satisfaction. Therefore, Recovery satisfaction also has significant and direct effect toward Trust. Perceived Justice has significant and direct effect toward Trust as well. Moreover, Recovery Satisfaction has positive effect as mediator between Perceived Justice and Trust in the study of Harris Hotel & Conventions Malang. Key Words: Perceived Justice, Service Recovery, Recovery Satisfaction, and Trust